Gender and governance issues in local government regional report of technical assistance in Bangladesh, Nepal, and Pakistan. - Asian Development Bank. South Asia Dept. (Manila South Asia Regional Dept., Asian Development Bank, 2004)
On women in politics and economic development and their empowerment issues dealt by ADB; a report.
Includes bibliographical references (p. [67]-68).
Keywords: Women in politics -- Bangladesh; Women in politics -- Nepal; Women in politics -- Pakistan; Women in economic development -- Bangladesh; Women in economic development -- Nepal; Women in economic development -- Pakistan